Materials development for speaking skills in aviation English for Malaysian air traffic controllers : theory and practice. - Paramasivam, Shamala (University of Nis, Serbia, 2013)
In 2004 the International Civil Aviation Organisation (ICAO) mandated that pilots and air traffic controllers the world over meet a set standard of language proficiency requirements as a safety measure against language- and communication-related problems in flying. In response to this mandate, aviation English training and testing initiatives mushroomed in industry. One of the challenges faced by aviation English practitioners was the lack of aviation-specific language learning materials to teach aspects of language. This paper presents in-house training materials that were developed through cooperation and collaboration with subject matter experts in aviation specifically to help a group of trainee air traffic controllers in Malaysia improve their spoken English particularly in fluency as a skill in speaking. The paper offers the theory and practice with regard to the decisions made about the rationale for and the sequencing of materials that underlie the process of materials development. The paper has relevance for ESP and ELT theory and practice with respect to materials development.